Exploring the intergenerational continuity of ACEs amongst a sample of Welsh male prisoners: A retrospective cross-sectional study - Kat Ford; Mark A. Bellis; Karen Hughes; Natasha Judd; Emma R. Barton (Child Protection and Practice)
Background: The relationship between parent and child adverse childhood experience (ACE) exposure remains underexplored, particularly within justice-involved samples. Objective: This objective of the study was to examine the intergenerational continuity of ACEs within a UK prison population. Participants: 294 males aged 18–69 years in a Welsh prison, with father reported data for 671 children they had fathered. Methods: A face-to-face ACE questionnaire measured exposure to 10 ACE types. For each child they had fathered participants were asked to report their child's gender, age and their exposure before the age of 18 to the same ACE types, except having a household member incarcerated. Findings: Paternal ACE exposure was found to increase the risk of child ACE exposure, both to multiple ACEs and individual ACE types. Compared to children of fathers with no ACEs, those of fathers with 4+ were almost three times more likely to have been exposed to 2–3 ACEs and six times more likely to be exposed to 4+ ACEs. The risk of a child residing in a household where mental illness was present was 7.4 times higher where their father had 4+ ACEs. Conclusion: Findings highlight the need for prevention interventions to break the intergenerational continuity of ACEs. Further research is needed to explore what protects against the intergenerational continuity of ACEs. Criminal justice systems and wider services need to ensure that they support those incarcerated alongside their families who are at high risk of ACEs and consequently poorer education, health and criminal justice outcomes.